2016
DOI: 10.12688/f1000research.9897.1
|View full text |Cite
|
Sign up to set email alerts
|

Pay-for-performance in resource-constrained settings: Lessons learned from Thailand’s Quality and Outcomes Framework

Abstract: Many countries have introduced pay-for-performance (P4P) Introduction. models to encourage health providers and institutions to provide good quality of care. In 2013, the National Health Security Office of Thailand introduced P4P, based on the UK Quality and Outcomes Framework (QOF), as a mandatory programme for primary care providers. This study aims to review the first year of the Thai QOF policy, focusing on the key features of its formulation and implementation stages.This study used a mix of data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, early evaluation of the program identified that the quality measures in use were perceived to have poor validity which negatively impacted upon the acceptability of the scheme, with resulting variation in uptake and financing at the local level [5]. In response, an independent research unit in the Ministry of Health-the Health Intervention and Technology Assessment Program (HITAP) was commissioned to develop and pilot potential quality indicators to be implemented in fiscal year 2017.…”
Section: Introductionmentioning
confidence: 99%
“…However, early evaluation of the program identified that the quality measures in use were perceived to have poor validity which negatively impacted upon the acceptability of the scheme, with resulting variation in uptake and financing at the local level [5]. In response, an independent research unit in the Ministry of Health-the Health Intervention and Technology Assessment Program (HITAP) was commissioned to develop and pilot potential quality indicators to be implemented in fiscal year 2017.…”
Section: Introductionmentioning
confidence: 99%